Missbruk och identitetsskapande : En litteraturstudie om missbrukande kvinnor - Eriksson, Ann-Charlotte (2015)
Drug abuse is found in all social classes and occurs among people of varying ages. Abuse creates both social and medical damages for those who abuse, which makes this problem a large social problem. In the thesis a theory about the creation of social identity and gender system is the basis.The purpose of this thesis is to, through a literature review, illustrate how addicted women's social identity is influenced by the immediate social context and how women's social subordination in society can consolidate a destructive social identity formation. The questions were: What are the main features of previous research regarding abuse of women's social interactions and identity formation? How can abusive women's social identity formation interpreted from a social psychological perspective and a gender perspective The methodology for collecting data was a literature search on Scopus, PsycINFO, ProQuest, and Luleå University's own database Primo. The results show that addicted women's social identity formation occurs with and within a group consisting of other drug users and that within the addiction culture there are unwritten rules, that make the women subordinate to men as in society at large. Validerat; 20150210 (global_studentproject_submitter)